Across the Taklamakan desert - Inoue, Shoji; Tagawa, Junzo; Tamai, Isao.; CCTV (China).; NHK Enterprises, Inc. (Japan). ([S.l.] NHK, 1990)
A panoramic tour on the ancient route to China travelled by Marco Polo, linking the ancient and modern day Asia. Explore the ancient Buddhist City of Miran, southeast of the legendary kingdom of Lou-Lan, the Chenchen near Kun-Lun mountains, the ruins of Ninja and the Taklamakan desert which means "the place from which nothing living returns!" Discover the art, culture and history that lives on in artifacts and the daily lives of its people in this most inaccessible regions.
VHS.
Music by Kitaro; Edited by Hiroyuki Shoji; Narrated by Graham Websters.
Keywords: Art, Chinese; Legends, Buddhist; Silk Road; China -- Antiquities; China -- Description and travel; China -- History; Takla Makan Desert (China).